Potential of Legetan Leaves (Acmella oleracea) as a Therapeutic Modality for Osteoarthritis: An In Vivo Study - Indrayani, Indrayani (HM Publisher, 2024)
Osteoarthritis (OA) is a degenerative joint disease characterized by inflammation and cartilage damage. Legetan leaves (Acmella oleracea) have anti-inflammatory and antioxidant potential that may help relieve OA symptoms. This study aims to evaluate the potential of legetan leaves as a therapeutic modality for OA in a rat model. Legetan leaf extract was formulated into an oral preparation and given to rats induced by OA with monosodium iodate. The positive control group received standard OA medications. Parameters measured include pain scores, joint inflammation, and cartilage damage. Legetan leaf extract significantly reduced pain scores and joint inflammation in rats with OA. Legetan leaf extract also shows a protective effect against cartilage damage. In conclusion, Legetan leaves have potential as a therapeutic modality for OA.